Estudio de la diversidad fenotípica y adaptación local en maíces nativos del norte argentino - Freilij, Damián; Defacio, Raquel Alicia; Heck, Mónica Isabel; Salve, Diego Antonio; Antonietta, Mariana; Fariza, Silvina Ines; De Lucia, Adrían Darío; Ferreyra, Mariana; Paniego, Norma Beatriz; Dominguez, Pia Guadalupe; Lia, Veronica Viviana (Instituto Nacional de Tecnología Agropecuaria (INTA), 2024)
Poster